1964
DOI: 10.1002/pol.1964.100020941
|View full text |Cite
|
Sign up to set email alerts
|

Free‐radical polymerization of olefins

Abstract: Propylene, butene‐1, isobutylene, 3,3‐dimethylbutene‐1, and tetradecene‐1 were polymerized at high pressures at 130–150°C. with dixy1tert‐butyl peroxide initiator to give low molecular weight polymers. Free radical copolymerization of propylene and isobutylene was also demonstrated. Facile chain transfer to give relatively stable radicals was blamed for the low rates and degrees of polymerization. The molecular weights were shown to be controlled by chain transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…The very low reactivity ratio of 1-Oct confirms the inability of the α-olefin radicals to react with α-olefin monomers, 78 and hence the inability of the α-olefin to homopolymerize via a radical pathway. 86 This is in line with the reactivity ratios determined for the controlled radical copolymerization of 1-Oct with conjugated comonomers, e.g. methyl methacrylate or acrylates, by ATRP.…”
Section: Vac/1-oct Copolymerizationsupporting
confidence: 82%
See 1 more Smart Citation
“…The very low reactivity ratio of 1-Oct confirms the inability of the α-olefin radicals to react with α-olefin monomers, 78 and hence the inability of the α-olefin to homopolymerize via a radical pathway. 86 This is in line with the reactivity ratios determined for the controlled radical copolymerization of 1-Oct with conjugated comonomers, e.g. methyl methacrylate or acrylates, by ATRP.…”
Section: Vac/1-oct Copolymerizationsupporting
confidence: 82%
“…83 Previous studies have demonstrated that the radical homopolymerization of 1-Oct is highly unfavored due to the formation of these stable allylic radicals, [83][84][85] and coupling reactions between polymer radicals and allylic radicals (Scheme S1 †). 86 These coupling reactions are expected to also occur during the VAc/1-Oct copolymerization.…”
Section: Vac/1-oct Copolymerizationmentioning
confidence: 99%
“…We first pursued development of reaction conditions that would promote the direct incorporation of quinine into a polymeric backbone via radical propagation of its α-olefin group. While degradative chain transfer and steric hindrance of the bulky quinuclidine ring were necessary challenges to overcome ( 52 – 54 ), the advantage to a direct approach is threefold: 1) Quinine can be used directly in a copolymerization reaction to enable a rapid, inexpensive, and scalable production method; 2) the quinuclidine amine can be protonated, aiding electrostatic interactions with DNA; and 3) the quinoline ring is distal from the backbone, which allows these polymer pendant groups to effectively intercalate into DNA without steric hindrance and allows reporting of binding and release via microscopic and spectroscopic methods.…”
Section: Resultsmentioning
confidence: 99%
“…Synthetic procedure for making functional olefins have been one of the major areas of interest of polymer chemist for that requires a unique technique that can copolymerize two different categories of monomers. 8 This area of enduring industrial importance has been explored by different scientific approach such as free radical polymerization, 9 Lewis acid-mediated polymerization, 10,11 palladium-based polymerization, [12][13][14][15] and of lately, controlled radical polymerization. [16][17][18][19][20] Copolymerization of acrylates with olefins through free radical polymerization route results in the formation of copolymers having very less incorporation of olefins.…”
Section: Introductionmentioning
confidence: 99%